Managing Blue Light Exposure: Impacts on Sleep Quality and Circadian Health - Alicja Grzelak (Quality in Sport)
Introduction: Blue light, a high-energy visible light emitted from natural and artificial sources, plays a crucial role in regulating circadian rhythms and sleep quality. While essential for maintaining alertness and synchronizing the biological clock, excessive exposure, especially during evening hours, disrupts melatonin production, adversely impacting sleep and overall health.